1984
DOI: 10.1029/jb089ib06p04026
|View full text |Cite
|
Sign up to set email alerts
|

Point defect chemistry of minerals under a hydrothermal environment

Abstract: The kinetics of rock/water interactions are sufficiently rapid that most hydrothermal systems in nature will be in equilibrium with the adjacent rock mass. The bulk rock chemistry buffers the fugacity of oxygen, which in turn fixes the fugacities of water and of hydrogen for a given pressure and temperature. Systems in which only water, oxygen, and hydrogen are present as fluid phases are considered here. Variations in the fugacity of oxygen by several orders of magnitude are possible locally, controlled by va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 50 publications
0
44
0
1
Order By: Relevance
“…Many experiments [3][4][5][6]19,28,32,34,35,38,[44][45][46][47][48][49][50][51][52][53][54][55][56] demonstrated that trace amount of water can weaken the creep strength for quartz and feldspar by one order of magnitude. Water enhances dislocation climb, recrystallization, and grain size reduction, which are considered to be the major deformation mechanism for developing ductile shear zones [19,37,38,51,54,55] .…”
Section: Weakening Effect Of Water On Flow Strength Of Ductile Shear mentioning
confidence: 99%
See 1 more Smart Citation
“…Many experiments [3][4][5][6]19,28,32,34,35,38,[44][45][46][47][48][49][50][51][52][53][54][55][56] demonstrated that trace amount of water can weaken the creep strength for quartz and feldspar by one order of magnitude. Water enhances dislocation climb, recrystallization, and grain size reduction, which are considered to be the major deformation mechanism for developing ductile shear zones [19,37,38,51,54,55] .…”
Section: Weakening Effect Of Water On Flow Strength Of Ductile Shear mentioning
confidence: 99%
“…The content of trace amount of water in minerals decreases with increasing metamorphic grade [13,[39][40][41][42][43] , suggesting decreasing water contents with increasing depth (temperature and pressure). Experiments at high temperature and high pressure indicate that trace amount of water can markedly weaken the creep strength of quartz [3][4][5][6]28,32,34,35,[44][45][46][47][48][49][50] , feldspar [19,38,51 -56] , feldspar-pyroxene hot-press aggregates [54] and granite [47] . The manifestation of the weakening effect on rock deformation includes enhanced strain rate, or lower creep strength and lower activation energy for higher water contents.…”
Section: Introductionmentioning
confidence: 99%
“…If hydrogen diffuses into the olivine lattice as a positively charged ion (or proton), it is expected to become associated with negatively charged point defects such as cation vacancies or anion interstitials (Hobbs 1984;Mackwell and Kohlstedt 1990). Hence, the solubility and speciation of hydrogen in a quasiternary mineral such as olivine should depend on the concentrations and the types of the point defects with which hydrogen ions become associated and, in turn, should be governed by the four independent thermodynamic parameters -temperature (T), total pressure (P), oxygen fugacity (fo2) and orthopyroxene activity (aopx) -for (Mg, Fe)2SiO4 olivine at fixed Mg:Fe ratio (Bai et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Es el denominado "debilitamiento hidrolítico" (Griggs, 1967;Blacic y Christie, 1984;Hobbs, 1984;Kronenberg et al, 1986). Los experimentos recientes demuestran que los medios hidrotermales son vías muy favo-rabIes para la difusión en el cuarzo de muy diversos tipos de defectos que rebajarían la resistencia de este mineral (Dennis, 1984;Etheridge et al, 1984;Kronenberg et al, 1986; entre otros).…”
Section: Etapas Deformativasunclassified